APLIKASI INFORMASI TEMPAT WISATA JAWA TENGAH BERBASIS ANDROID (Information Technology and Telematics, 2014)
Abstract- Central Java Province as one of the tourism destinations in Indonesia offers various tourist attractions both natural, cultural, tourist and man-made, which is very impressive as witnessing the wonders of the world such as Borobudor temple, Prambanan temple and a wide variety of interesting tour. Most tourists come to Central Java to see Javanese culture and tradition is still strong. Tourism for the Government of Central Java is one aspect to increase local revenue. One of the constraints faced by local government in terms of tourism development is the lack of an effective information system for tourists. System development method used in this study is a prototype consisting of analysis, design, create prototypes, evaluation and improvement, results. System design using OOD consisting of use case diagrams and activity diagrams. Programming using Java programming and Android .The end result of this research is the application of information-based tourist attractions in Central Java android can be used to display information sights consist of images, profiles and etymology tourist attractions in the form of text and location in google map form Keywords - Places Of Interest, Central Java, Android, Prototype, Java